Integrasi Edukasi, Kampanye, dan Policy Brief dalam Strategi Komunikasi Pembangunan - Eva Riyanty Lubis; Mhd. Latip Kahpi (Sinergi : Jurnal Ilmiah Multidisiplin, 2025)
This study addresses the persistent gap in development communication research regarding the lack of integrated strategic frameworks that connect community education, public campaigns, and evidence-based policy advocacy. While existing studies often examine these components separately, limited attention has been given to how their systematic integration can enhance participatory and sustainable development outcomes. Employing a qualitative conceptual approach, this study analyzes key theories of development communication and applies them through a simulated strategic communication design that integrates education, campaign activities, and policy briefs. The findings demonstrate that an integrated communication strategy strengthens community capacity, increases public engagement, and facilitates stronger linkages between grassroots initiatives and policy decision-making processes. Education functions as the foundation for knowledge and empowerment, campaigns mobilize public participation and shape social norms, and policy briefs translate community-level evidence into actionable policy recommendations. This study contributes to development communication scholarship by proposing an integrative strategic model that positions communication not merely as an information tool but as a transformative mechanism linking social participation, behavioral change, and policy support within sustainable development processes. Keywords: Development communication; strategic communication; community education; public campaigns; policy brief; participatory development. Abstrak Penelitian ini mengkaji kesenjangan dalam kajian komunikasi pembangunan yang masih cenderung memisahkan peran edukasi, kampanye publik, dan advokasi kebijakan, sehingga belum menghasilkan kerangka strategi komunikasi yang terintegrasi dan berkelanjutan. Ketiga instrumen tersebut berpotensi saling melengkapi dalam mendorong partisipasi masyarakat dan penguatan kebijakan publik. Penelitian ini menggunakan pendekatan kualitatif konseptual melalui analisis teori komunikasi pembangunan serta simulasi rancangan strategi komunikasi yang mengintegrasikan edukasi, kampanye, dan policy brief. Hasil kajian menunjukkan bahwa strategi komunikasi pembangunan yang terintegrasi mampu meningkatkan kapasitas masyarakat, memperkuat keterlibatan publik, serta menjembatani hubungan antara inisiatif berbasis komunitas dan proses pengambilan kebijakan. Edukasi berfungsi sebagai fondasi pemberdayaan, kampanye berperan dalam mobilisasi dan pembentukan opini publik, sementara policy brief menjadi sarana advokasi berbasis bukti. Penelitian ini berkontribusi dengan menawarkan model strategis komunikasi pembangunan yang memposisikan komunikasi tidak hanya sebagai alat penyampaian informasi, tetapi sebagai mekanisme transformatif yang menghubungkan partisipasi sosial, perubahan perilaku, dan dukungan kebijakan dalam pembangunan berkelanjutan. Kata kunci: Komunikasi pembangunan; strategi komunikasi; edukasi masyarakat; kampanye publik; policy brief; pembangunan partisipatif